2019
DOI: 10.1002/14651858.cd004290.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Target of rapamycin inhibitors (TOR-I; sirolimus and everolimus) for primary immunosuppression in kidney transplant recipients

Abstract: Target of rapamycin inhibitors (TOR-I; sirolimus and everolimus) for primary immunosuppression in kidney transplant recipients (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 257 publications
0
31
0
Order By: Relevance
“…However, mTORi use in kidney transplantation is associated with inferior graft survival 14 , 15 and increased mortality risk 16 , 17 . In recent meta-analysis, Wolf S. et al found that initiation of mTORi within 3 months of kidney transplantation may reduce the future risk of malignancy 18 but in Hahn et al analysis, mTORi treatment failed to demonstrate a reduction in cancer risk 19 . These controversial results regarding the role of mTORi and timing of introduction in transplant outcomes need further evidence for verification.…”
Section: Introductionmentioning
confidence: 99%
“…However, mTORi use in kidney transplantation is associated with inferior graft survival 14 , 15 and increased mortality risk 16 , 17 . In recent meta-analysis, Wolf S. et al found that initiation of mTORi within 3 months of kidney transplantation may reduce the future risk of malignancy 18 but in Hahn et al analysis, mTORi treatment failed to demonstrate a reduction in cancer risk 19 . These controversial results regarding the role of mTORi and timing of introduction in transplant outcomes need further evidence for verification.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is ongoing controversy regarding the effectiveness of these combinations [13,14,17,[42][43][44]. Some clinical trials [45] support the use of everolimus as a standard immunosuppressive drug leading to reduced exposure to CNI; however, this is not universal. A recent systematic review [45] which compared mTOR with other immunosuppressants found that everolimus or sirolimus combined with a CNI prevented kidney transplant failure and rejection as effectively as other immunosuppressants combined with a CNI in short follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical trials [45] support the use of everolimus as a standard immunosuppressive drug leading to reduced exposure to CNI; however, this is not universal. A recent systematic review [45] which compared mTOR with other immunosuppressants found that everolimus or sirolimus combined with a CNI prevented kidney transplant failure and rejection as effectively as other immunosuppressants combined with a CNI in short follow-up periods. However, the risk of viral infections (cytomegalovirus and BK) was significantly less with mTOR combined with everolimus.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published Cochrane review of 70 studies in adult KTRs found mTORi/antiproliferative regimens compared with CNI/antiproliferative regimens had little or no difference in death or malignancies, but mTORi based regimens were associated with lower rates of CMV infection and increased incidence of graft loss and AR. When CNI/mTORi regimens were compared with CNI/antiproliferative regimens, little or no difference was found in death (RR = 1.06, 95% CI = 0.84–1.33; 31 studies), graft loss (RR = 1.09, 95% CI = 0.82–1.45; 26 studies), AR (RR = 0.95, 95% CI = 0.81–1.12; 24 studies), or malignancies (RR = 0.83, 95% CI = 0.64–1.07; 17 studies), and again reduction in CMV (RR = 0.44, 95% CI = 0.34–0.58; 25 studies) was found 96 . Such robust pooled data are not available for pediatric KTRs.…”
Section: Maintenance Immunosuppression In Pediatric Kidney Transplantmentioning
confidence: 95%